Development of bismuth titanate for wireless dielectric antenna application - Al-Amani, Umar (2009)
Perovskite structure of bismuth titanate (is referred as undoped sample)and neodymium doped-bismuth titanate (is referred as doped sample) has been studied to see the potential as dielectric antenna for wireless application. * more details in paper